Scarred Communities Psychosocial Impact of Man-made and Natural Disasters on Sri Lankan Society - Somasundaram, Daya (New Delhi, India Sage, 2014)
Scarred Communities is a qualitative, psycho-ecological study of the long-term effects of disasters-both man-made and natural-on Sri Lankan communities.
Keywords: Disasters -- Psychological aspects -- Sri Lanka; Psychoanalytic counseling -- Sri Lanka